Performance of oilseeds in India: A temporal study: Performance of oilseeds in India: A temporal study - S V RAMANA RAO; D VAISHNAVI SANKARI; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
In India, oilseeds are cultivated on an area of 26 million ha with a production of 29.65 million tonnes primarily under rainfed conditions. Oilseeds production could not keep pace with the growing demands due to changing life style, increasing population and rising per capita income resulting to dependency on imports. The CAGR revealed that across different periods, despite fluctuations in the rate of growth in area, yield contributed to change in production thus suggesting the power of technologies operational at the farm. Multi-pronged strategy through institutional refurbishments for technology assemblage, favourable tariff policy and public private partnerships on seed production, output marketing and value chains needs strengthening for enhancing the domestic production and productivity.